The Relationship Between Self-Regulation and Academic Procrastination of Students - Putri Alivia; Mori Dianto; Wira Solina (Universitas PGRI SUMATERA BARAT, 2024)
AbstractThis research is motivated by the presence of students who tend to procrastinate on assignments given by the teacher, thereby disrupting their learning process. That happens because self-management among students is lacking, as self-management in terms of learning is necessary. The purpose of this research is to describe: 1) The profile of students' self-regulation. 2) The profile of students' academic procrastination. 3) To examine the relationship between self-regulation and students' academic procrastination. Paraphrase text. This research uses a descriptive correlational quantitative method with a population of 348 students. The sample in this study consisted of 186 people using the proportional random sampling technique. The instruments used in this study are the academic procrastination questionnaire and the self-regulation questionnaire. Data analysis in this study is descriptive statistics and product moment correlation. The results of the research on the relationship between self-regulation and academic procrastination of twelfth-grade students at Padang State High School 3 reveal that: 1) The self-regulation profile of the students is in the moderate category. 2) The academic procrastination profile of the students is in the moderate category. 3) There is a very weak correlation between self-regulation and academic procrastination of the students.